High‐resolution magnetic signature of active hydrothermal systems in the back‐arc spreading region of the southern Mariana Trough. Issue 5 (4th May 2015) - Fujii, Masakazu; Okino, Kyoko; Honsho, Chie; Dyment, Jerome; Szitkar, Florent; Mochizuki, Nobutatsu; Asada, Miho
Abstract High‐resolution vector magnetic measurements were performed on five hydrothermal vent fields of the back‐arc spreading region of the southern Mariana Trough using Shinkai 6500, a deep‐sea manned submersible. A new 3‐D forward scheme was applied that exploits the surrounding bathymetry and varying altitudes of the submersible to estimate absolute crustal magnetization. The results revealed that magnetic‐anomaly‐derived absolute magnetizations show a reasonable correlation with natural remanent magnetizations of rock samples collected from the seafloor of the same region. The distribution of magnetic‐anomaly‐derived absolute magnetization suggests that all five andesite‐hosted hydrothermal fields are associated with a lack of magnetization, as is generally observed at basalt‐hosted hydrothermal sites. Furthermore, both the Pika and Urashima sites were found to have their own distinct low‐magnetization zones, which could not be distinguished in magnetic anomaly data collected at higher altitudes by autonomous underwater vehicle due to their limited extension. The spatial extent of the resulting low magnetization is approximately 10 times wider at off‐axis sites than at on‐axis sites, possibly reflecting larger accumulations of nonmagnetic sulfides, stockwork zones, and/or alteration zones at the off‐axis sites.